LEC-2, a highly variable lectin in the lichen Peltigera membranacea - Manoharan, Sheeba S. (Springer Netherlands, 2012)
Lectins are a diverse group of carbohydrate binding proteins often involved in cellular interactions. A lectin gene, lec-2, was identified in the mycobiont of the lichen Peltigera membranacea. Sequencing of lec-2 open reading frames from 21 individual samples showed an unexpectedly high level of polymorphism in the deduced protein (LEC-2), which was sorted into nine haplotypes based on amino acid sequence. Calculations showed that the rates of nonsynonymous versus synonymous nucleotide substitutions deviated significantly from the null hypothesis of neutrality, indicating strong positive selection. Molecular modeling revealed that most amino acid replacements were around the putative carbohydrate-binding pocket, indicating changes in ligand binding. Lectins have been thought to be involved in the recognition of photobiont partners in lichen symbioses, and the hypothesis that positive selection of LEC-2 is driven by variation in the Nostoc photobiont partner was tested by comparing mycobiont LEC-2 haplotypes and photobiont genotypes, as represented by the rbcLX region. It was not possible to pair up the two types of marker sequences without conflicts, suggesting that positive selection of LEC-2 was not due to variation in photobiont partners.